A alegoria histórica em Manoel de Oliveira: um filme falado - Santos, Wiliam Pianco dos (2011)
This research consists of a discourse analysis of Um filme falado (2003), from the Portuguese film director Manoel de Oliveira. The idea is to investigate the meanings implied in the historical allegory built by the director in that film, questioning the notions of nation and globalization. In this sense, the theoretical references are conducted to the implications of the allegory in cinematographic discourse, as well as the interdisciplinary field located between the Cinema and History. For such end, thematic and formal aspects will be dealt based on the film analysis of the work in question.